Pengaruh Metode Pembelajaran dan Gaya Belajar terhadap Kemampuan Berpikir Kritik Biologi - Subhan Harie (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2015)
The aim of this study was to determine 1) The interaction effect between teaching methods and learning styles of the ability to think criticism biology, 2) Critical thinking skills of biology that uses the learning Problem Solving and Problem Posing, and, 3) Critical thinking skills biology to has studied the style of visual, auditory and kinesthetic learning styles. The method used is experiment. Affordable population are students of class IX in south Jakarta SMPN 131 is 198 students. Samples numbered 72 students. The sampling technique was multistage sampling. The instrument used is a biological test critical thinking skills and test results learners learning styles questionnaire. The data analysis using descriptive statistics and analysis of variance (ANOVA) in both directions. The results of the study hypothesis was obtained conclusions: 1) There is no interaction effect between teaching methods and learning styles on learning outcomes biology students. Interaction analysis using ANOVA obtained Fo = 2.235 and Sig. = 0.115> 0.05 at the 5% significance level. 2) There is a learning method influence on the ability to think criticism. Results of the analysis of data between classes using ANOVA obtained Fo = 20.309 and Sig. = 0.000 <0.05 at the 5% significance level. 3) There is no learning styles influence on the ability to think criticism biology. The results of data analysis using ANOVA obtained Fo = 0.414 and Sig. = 0.663> 0.05 at the 5% significance level. Keywords: Method of Learning, Learning Styles, Thinking Criticism.